ADVANCING PUBLIC PROCUREMENT FINANCE: THE METALLURGICAL COMBINE OF UZBEKISTAN EXPERIENCE (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article delves into the advancements in public procurement finance, focusing on the experiences of the Metallurgical Combine of Uzbekistan. Public procurement plays a critical role in economic development, and efficient financial management within this sector can significantly enhance national growth. The study highlights the unique strategies employed by the Metallurgical Combine of Uzbekistan to optimize procurement processes, ensure fiscal discipline, and promote transparency. By examining the frameworks and methodologies adopted, this article provides valuable insights into best practices that can be replicated in similar industrial contexts. Additionally, it addresses the challenges faced and the innovative solutions implemented to overcome them, offering a comprehensive overview of how public procurement finance can be advanced through strategic planning and execution.